Aplikasi HOT-Day: Hadits of the Day Sebagai Media Edukasi Pengamalan Hadits - Dina Maulidiya; Isnaeni Musarofah; Rizki Siti Hasnani; Ani Nur Aeni (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
The rapid development of technology brings both positive and negative impacts that greatly affect human life. especially among children. However, if it is properly combined with current technology, it will not affect children in a negative way. Children's interest in memorizing hadith is currently very low. To increase children's interest in memorizing, we created a product called HOT-DAY. By making the HOT-DAY application, it is hoped that it can bring children to become people who have noble character. In addition to memorizing hadith, this application will also teach children to implement the morals and behaviors recommended in the related hadith. This study uses a Design and Development (D&D) research model, and the data collection method is carried out through literature studies, questionnaires, and interviews. The results after testing with 3rd grade elementary school children show that the HOT-DAY application has functioned well and the responses from the respondents are very enthusiastic. This application attracts children's attention to increase memorization and implement hadith in everyday life. The presence of this HOT-DAY application can be a guide in children's lives as well as a learning medium for teachers at school and parents at home to educate their children on improving their morals and morals.